Perfil imunológico associado à susceptibilidade, resistência e cura na infecção por Leishmania ( Leishmania ) infantum - Galvão, Joanna Gardel Valverde (2014)
Visceral Leishmaniasis (VL) is endemic in Brazil and the northeast region had the highest incidence of the disease , despite, in the last 30 years, it has spread to all geographic regions of the country. Leishmania infantum is the m ain etiological agent of VL in Latin America, Europe and North Africa. However, not all infected individuals develop the disease; in fact, the majority present spontaneous re solution of infection without symptoms. The evaluation of the immunological profil e has been mostly conducted stimulating, with Leishmania spp. antigen, peripheral blood mononuclear cells isolated from subjects with VL. These studies showed that VL patients had an inhibition of both, lymphocyte proliferation and proinflammatory response to Leishmania spp. antigen. Our study aimed to evaluate the immune response in active LV, cured post treatment and asymptomatic infection. To reach this aim, we analyzed immunophenotypic features related to activation, Treg and memory lymphocytes, by flow cytometry, as well as, evaluation of cytokine production, in ex vivo or in whole blood culture. In active VL volunteers, a longitu dinal study was conducted with reassessment at 4 and 14 months after clinical cure. The control group included individuals th at live d in endemic region and were either Positive Control, consisting of individuals with positive anti - L eishmania spp. serology and/or positive PCR for Leishmania  spp. and Negative Control composed by individuals with negative anti - Leishmania antibodie s serology and negative PCR for Leishmania . During VL, CD4 lymphocytes showed greater activation and memory profile s and were the major source of cytokines in culture when compared to CD8 lymphocytes , and these were not Leishmania specific. There were act ivated lymphocytes during VL (CD4 + CD69 + :4.9%) when compared to control groups, Positive (CD4 + CD69 + :1.96%, p=0.0045) and Negative (CD4 + CD69 + :1.35%, p=0.006), on the other hand, this was non - specific activation. The lymphocyte activation profile remain ed el evated even 14 months post treatmen t. A fter clinical cure , the activation was Leishmania specific (CD4 + CD25 + absence of SLA: 8.4%, and presence of SLA: 10.7% p=0.0279). CD8 + CD25 + lymphocytes were able to produce Leishmania specific IFN - γ in both, Positive Controls (absence of SLA 5.2% and presence of SLA: 9.5%, p=0.0391) and Cured 4 month (absence of SLA: 3.9%; presence of SLA: 10.7% p=0.0098). Whole blood culture cells, of VL patients, were able to produce IFN - γ, by SLA stimulation (absence of SLA: 28.0 pg ∕mL, and presence: 44.3 pg∕mL p=0.0020) as well as recovered groups (absence of SLA 2.3 pg∕mL and presence of SLA 139.8 pg∕mL, p=0.0005). However, the high level of IL - 10 seem ed to inhibit pro - inflammatory activity of IFN - γ and TNF - α during symptomatic dis ease . Unlike other pro - inflammatory cytokines, active VL group d id not produce Leishmania specific IL - 2 (absence of SLA 2.4 pg∕mL and presence of SLA: 2.6 pg∕mL). Based on these data we conclude that the restoration of lymphocyte activation and decreased i n IL - 10 Leishmania specific production were related to a protective immune profile.